2013
DOI: 10.1177/0954406213517376
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation into balancing high-speed flexible shafts, by the use of a novel compensating balancing sleeve

Abstract: Traditional techniques for balancing long, flexible, high-speed rotating shafts are inadequate over a full range of shaft\ud speeds. This problem is compounded by limitations within the manufacturing process, which have resulted in increasing\ud problems with lateral vibrations and hence increased the failure rates of bearings in practical applications. There is a need\ud to develop a novel strategy for balancing these coupling shafts that is low cost, robust under typically long-term operating\ud conditions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…The presented account extends previous, special case, research 14 on compensating balancing sleeves, to demonstrate the suitability of the methodology when applied to a generalised case of a shaft loaded with a single concentrated imbalance. By extension, it is shown that the principle of superposition allows for more practical imbalance distributions to be analysed using vector addition of any number of individual concentrated imbalances, of various magnitude/position.…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations
“…The presented account extends previous, special case, research 14 on compensating balancing sleeves, to demonstrate the suitability of the methodology when applied to a generalised case of a shaft loaded with a single concentrated imbalance. By extension, it is shown that the principle of superposition allows for more practical imbalance distributions to be analysed using vector addition of any number of individual concentrated imbalances, of various magnitude/position.…”
Section: Resultsmentioning
confidence: 57%
“…Shear Force Reaction Ratio, RR This can be determined more readily by considering the special case of uniform eccentricity, 14 for simply supported and encastre supported ends.…”
Section: Equivalent Value Of Eccentricity Resulting From Encastre Simmentioning
confidence: 99%
See 2 more Smart Citations
“…This is typically done using a series of fixed balancing flanges on the shaft. Knowles et al proposed an alternative method in which balance corrections are applied to the free ends of a pair of balancing sleeves, attached to each end of the rotating shaft [11,12].…”
Section: Introductionmentioning
confidence: 99%